Steady State Magnetic Resonance Angiography of the Thoracic Aorta Using Inversion-recovery Steady-State Free Precession and a High Relaxivity Contrast Agent. Issue 6 (November 2020) - Abbasi, Muhannad Aboud; Serhal, Ali; Reese, Olivia; Aouad, Pascale; Collins, Louise; Blaisdell, Julie; Collins, Jeremy; Carr, James
Abstract : Purpose: To evaluate image quality and aortic dimension measurement accuracy of high resolution, motion compensated steady-state magnetic resonance angiography (SS-MRA) with a high relaxivity, extracellular fluid gadolinium-based contrast agent compared with standard first-pass contrast enhanced MRA (FP-CEMRA) in patients with thoracic aortic aneurysms. Materials and Methods: Sixty-nine patients (mean age, 51.7 y, 25% female) diagnosed with thoracic aortic aneurysms who underwent MRA on a 1.5 T scanner using FP-CEMRA and SS-MRA techniques were retrospectively identified. Quantitative analysis was performed by measuring the aortic diameters at 6 locations within the thoracic aorta for each technique. Two radiologists independently performed the qualitative analysis by assessing the image quality (1 to 5), presence of artifact (1 to 4), signal-to-noise (1 to 4), contrast-to-noise (1 to 4), and wall conspicuity (1 to 4) in the aorta at 4 different locations: the aortic root, the ascending aorta, the aortic arch, and the descending aorta. Results: The aortic dimensions obtained by SS-MRA had a good correlation with FP-CEMRA. Means for the aortic diameters between the FP-CEMRA and the SS-MRA at all 6 locations demonstrated minimal mean differences (0.013 to 0.044 mm). Qualitative assessment of aorta at 4 locations by 2 reviewers demonstrated that SS-MRA had on average superior image quality at the aortic root and ascending aorta for both reviewers ( P <0.05) and at the descending aorta for one reader ( P <0.05). Otherwise, both techniques were comparable at the ascending aorta. SS-MRA demonstrated less artifact at the aortic root and the ascending aorta ( P <0.05). Conclusion: Aortic dimension measurements provided by SS-MRA with a high relaxivity, extracellular fluid gadolinium-based contrast agent are comparable to the conventional FP-CEMRA. Furthermore, SS-MRA qualitatively demonstrated comparable to better overall image quality than FP-CEMRA at different aortic locations. Therefore, SS-MRA may provide a comparable alternative, or complementary examination to conventional FP-CEMRA in patients who have difficulty breath holding, or in situations where contrast bolus timing was poor.